The Effect of Soybean, Turmeric, and Tamarind Phytotherapy on Dysmenorrhea in Adolescent Girls - Lailatul Mutammamah; Nyna Puspita Ningrum (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Adolescents commonly experience reproductive health problems, with Premenstrual Syndrome (PMS) and dysmenorrhea being the most prevalent. Dysmenorrhea, characterized by severe lower abdominal and back pain, affects 54.89% of Indonesian adolescents, with 15% experiencing activity limitations due to pain. In East Java, 64.25% of adolescents suffer from dysmenorrhea, with 54.89% experiencing primary dysmenorrhea.This study investigates the effect of a soybean, turmeric, and tamarind phytotherapy combination on dysmenorrhea in adolescent girls. A quasi-experimental design with a pretest-posttest control group was conducted on 48 female students from SMP 02 Bangkalan (24 treatment, 24 control), selected through random sampling. The Wilcoxon Signed Ranks Test and Mann-Whitney U-Test were used for analysis.Results revealed that 58.3% of the treatment group reported mild pain, while 54.2% of the control group experienced moderate pain. Statistical tests showed a significant effect (p = 0.000, p < 0.05), confirming the effectiveness of phytotherapy in reducing dysmenorrhea. This study suggests increasing education on phytotherapy as an alternative menstrual pain treatment for adolescents